2014
DOI: 10.1002/rcm.6833
|View full text |Cite
|
Sign up to set email alerts
|

Laser desorption time‐of‐flight mass spectrometry of atomic switch memory Ge2Sb2Te5 bulk materials and its thin films

Abstract: This is the first report that elucidates the stoichiometry of Gem Sbn Tep clusters formed in plasma when bulk or nano-layers of GST material are ablated. The clusters were found to be fragments of the original structure. The results might facilitate the development of PLD technology for this memory phase-change material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…It has been already shown that Laser Desorption Ionization Time‐of‐Flight Mass Spectrometry (LDI TOFMS) is a powerful and useful technique to generate and study clusters of various solid materials including chalcogenide glasses; it was demonstrated that this technique can help to determine structural fragments of As–Se and Ga–Ge–Sb–S materials in solid as well as in plasma state . The phase change memory Ge 2 Sb 2 Te 5 bulk materials, their thin films, and Ge–As–Te materials were also analysed by LDI TOFMS …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been already shown that Laser Desorption Ionization Time‐of‐Flight Mass Spectrometry (LDI TOFMS) is a powerful and useful technique to generate and study clusters of various solid materials including chalcogenide glasses; it was demonstrated that this technique can help to determine structural fragments of As–Se and Ga–Ge–Sb–S materials in solid as well as in plasma state . The phase change memory Ge 2 Sb 2 Te 5 bulk materials, their thin films, and Ge–As–Te materials were also analysed by LDI TOFMS …”
Section: Introductionmentioning
confidence: 99%
“…16,17 The phase change memory Ge 2 Sb 2 Te 5 bulk materials, their thin films, and Ge-As-Te materials were also analysed by LDI TOFMS. 18,19 In this study, LDI TOFMS technique was therefore used for the analysis of (GeSe 2 ) 100Àx (Sb 2 Se 3 ) x bulk glasses to obtain information about the structural fragments (and their contamination by oxygen and/or hydrogen, eventually) present in the plasma arising from interaction of pulsed laser with solid-state material. The knowledge gained should contribute to a better understanding of the fabrication and properties of thin (GeSe 2 ) 100Àx (Sb 2 Se 3 ) x amorphous films prepared by plasma deposition techniques, especially by pulsed laser deposition.…”
Section: Introductionmentioning
confidence: 99%
“…26 It has been demonstrated that Laser Desorption Ionization Time-of-Flight Mass Spectrometry (LDI TOFMS) is a strong experimental method for the generation and identification of clusters of diverse solid state materials inclusive of amorphous chalcogenides as well as for the assessment of their contamination (oxygen, hydrogen and/or carbon impurities). 27,28 In present work, Ge-As-Se glasses and PLD thin films were analysed through LDI A c c e p t e d m a n u s c r i p t TOFMS in order to acquire information regarding the structural fragments (and their contamination) present in the plasma emerging from the interaction of pulsed laser with solid state material.…”
mentioning
confidence: 99%
“…Features of germanium such as variable valence (II and/or IV), potential for catenation, and the ability to form ions of cyclic and three‐dimensional (3D) structures may provide the basis for the occurrence of negatively or positively charged Ge x and Ge x H m clusters in mass spectra . Laser ablation ionization of germanium, in spite of it being of high purity (99.9999%), leads to the formation of high numbers of clusters, where a small number of Ge m clusters is accompanied by high number of Ge m H n clusters (up to m/z 1000) . Germanium also forms several hydrides with 3D cyclic structures, such as tetragermatetrahedrane (Ge 4 H 4 ), hexagermaprismane (Ge 6 H 6 ), octagermacubane (Ge 8 H 8 ), dipentagermaprismane (Ge 10 H 10 ), octagermaprismane (Ge 8 H 8 ), and other polygermanes .…”
mentioning
confidence: 99%
“…[23] Laser ablation ionization of germanium, in spite of it being of high purity (99.9999%), leads to the formation of high numbers of clusters, where a small number of Ge m clusters is accompanied by high number of Ge m H n clusters (up to m/z 1000). [24] Germanium also forms several hydrides with 3D cyclic structures, such as tetragermatetrahedrane (Ge 4 H 4 ), hexagermaprismane (Ge 6 H 6 ), octagermacubane (Ge 8 H 8 ), dipentagermaprismane (Ge 10 H 10 ), octagermaprismane (Ge 8 H 8 ), and other polygermanes. [23] The tendency is for the mass spectra of higher hydrides to be dominated by ions with high metal content, resulting from the successive elimination of hydrogen molecules.…”
mentioning
confidence: 99%